Excess of deaths classified with garbage codes in the COVID-19 pandemic - Araújo da Silva, Everlane Suane (2023)
In the disaster scenario witnessed during the pandemic caused by COVID-19, the act of defining the underlying cause of a death was no trivial matter and the increased use of Garbage Codes (poorly defined or not very specific codes) raises concerns regarding the quality of the information on causes of death in the states of Brazil. There was a significant increase in the number of deaths during the pandemic in the state of Paraíba, located in the Northeast region of Brazil, a situation similar to the national context. There were 31,107 deaths in 2020 in Paraíba, while an average of 27,000 deaths were identified for the period 2015 to 2019. Our goal was to identify and measure the excess of deaths classified with Garbage Codes in the COVID-19 pandemic in the geographic space of the state of Paraíba in 2020. The time series of deaths were obtained from the Mortality Monitoring Panel for Unspecific or Incomplete Basic Causes (Garbage Codes) of the Ministry of Health, for all months of the years 2015 to 2020. Projections of total deaths and deaths by Garbage Codes (GC) were calculated. The calculation of the excess proportion of deaths classified by Garbage Codes in the state of Paraíba resulted in 8.58%, highlighting the month of June 2020, which reached the maximum value equal to 19.42%. We expect to contribute to advance knowledge regarding the current reality of quality information on death notifications in an area of the country that seeks to make progress in this direction and to highlight the need for research in other locations in Brazil.